Peningkatan Keterampilan Berpikir Kritis melalui Model Discovery Learning pada Mata Pelajaran Sosiologi - Siti Mahmudatul Banat (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Students' critical thinking skills are the problem in this research. The aim of implementing this classroom action research is to improve students' critical thinking skills through the discovery learning model and find out the application of the discovery learning model to improve students' critical thinking skills in sociology subjects. The respondents in this study were class XII IPS 2 SMA Negeri 1 Sentolo consisting of 35 students. The measuring instruments used are critical thinking skills instruments, student observation sheets, and teacher observation sheets. Data analysis techniques using descriptive statistics using percentage formulas. The criteria for the success of the action is learning to improve critical thinking skills. This is said to be successful if students have achieved a minimum of medium criteria or 75 and the number of students who achieved a medium score reaches 80%. The critical thinking skills assessment measuring tool is 5 (five) points, then the criteria are determined. The results of this research are the discovery learning model can improve students' critical thinking skills in Sociology subjects, and the application of discovery learning with scaffolding in the form of individual and group activity guides as well as group division by placing students who can lead their friends can improve critical thinking skills students in Sociology subjects. The increase in critical skills in student activities in cycle 1 was 50.63%, in cycle 2 it was 77.51% or 26.88%. Meanwhile, the assessment of critical thinking skills increased in cycle 1 with an average score of 65.47, in cycle 2 it became 83.24, or 17.77.